(untitled) (Research, Society and Development, 2021)
The objective of this study was to identify elements relatives to the didactic-methodological aspects used by the teacher to dyslexic students, involving the initial and continuing training of teachers, teaching experience, training carried out in the area of ​​dyslexia, resources used in the classroom and suggestions for activities. Dyslexia is considered a Specific Learning Disorder, according to the American Psychiatric Association. It was a field research aimed at elementary school teachers in public schools in the city of João Pessoa, Paraíba. Therefore, 78 teachers participated, answered the ten questions of the applied questionnaire, through google forms. 90% have lato sensu courses, while 10% strictu sensu. 75% work for more than ten years as teacher, 15% between one and five years and 10% less than a year. 25% assured that they had never studied dyslexia, 55% that the subject was little explored, 15% believed that they studied regularly, and, finally, 5% believed that the topic was explored significantly. 23% answered that they do not feel capable of dealing with dyslexics, 28% stated that yes and 49% said that maybe. 65% said already used various activities to apply to subjects with dyslexia and 35% said did not. As in other professions, teachers need to be constantly trained to deal with the obstacles encountered in their workday, as teaching requires preparation, motivation and adequate training. Therefore, dealing with dyslexic children requires initial or continuous training directed to these subjects.